Improved SED-fitting Assumptions Result in Inside-out Quenching at z ~ 0.5 and Quenching at All Radii Simultaneously at z ~ 1 - Alexander de la Vega; Susan A. Kassin; Camilla Pacifici; Stéphane Charlot; Emma Curtis-Lake; Jacopo Chevallard; Timothy M. Heckman; Anton M. Koekemoer; Weichen Wang (The Astrophysical Journal)
Many studies conclude that galaxies quench from the inside-out by examining profiles of specific star formation rate (sSFR). These are usually measured by fitting spectral energy distributions (SEDs) assuming a fixed dust law and uniform priors on all parameters. Here, we examine the effects of more physically motivated priors: a flexible dust law, an exponential prior on the dust attenuation A _V , and Gaussian priors that favor extended star formation histories. This results in model colors that better trace observations. We then perform radial SED fits to multiband flux profiles measured from Hubble Space Telescope images for 1440 galaxies at 0.4 <  z  < 1.5 of stellar masses 10 ^10 –10 ^11.5 M _⊙ using both the traditional and the more physically motivated assumptions. The latter results in star formation rate and A _V profiles that agree with measurements from spectroscopy and A _V profiles that behave correctly as a function of inclination. Since green valley galaxies at z ∼ 1.3 are expected to evolve into quiescent galaxies at z ∼ 0.9, we compare their sSFR profiles using the more physically motivated assumptions. Their slopes are similar at all masses (0.06–0.08 dex kpc ^−1 ), and the normalizations for the quiescent galaxies are lower. Therefore, the sSFR profiles decline with time as quenching occurs at all radii simultaneously. We compare profiles of green valley galaxies at z ∼ 0.9 and quiescent galaxies at z ∼ 0.5. The former are shallower at all masses by ~0.1 dex kpc ^−1 . The sSFR profiles steepen with time as galaxies quench from the inside-out. In summary, galaxies at z ∼ 1 quench at all radii simultaneously while galaxies at z ∼ 0.7 quench from the inside-out.